PELATIHAN PENDEKATAN INTERDISIPLINER BAGI GURU PAI DALAM MENJAWAB ISU KONTEMPORER - Lina Nuriklima; Mugni Muhit (Jurnal Istimā, 2025)
This community service program was implemented in response to the challenges faced by Islamic Education Teachers (PAI) at SDN 01 Sukajadi. The main challenge was the difficulty in providing comprehensive answers to students' questions about contemporary issues, such as radicalism, gender equality, and the environment. To overcome this, the activity was designed with the main objective of improving the capacity of teachers in applying an interdisciplinary approach through intensive training. The method used was a participatory workshop, designed with an andragogical approach to meet the learning needs of adults. This activity was carried out in two sessions, on October 13 and 22, 2025. The evaluation results showed significant achievements, with an 85% increase in participants' understanding of the concept of an interdisciplinary approach. In practical terms, 90% of participants were also declared capable of developing integrated learning plans. Another success was the development of 15 innovative learning modules that integrate Islamic values with social sciences and science. Based on these achievements, it can be concluded that this interdisciplinary approach training has proven effective in improving the competence of PAI teachers. This increase in competence enables them to respond to contemporary educational challenges more contextually and comprehensively, thereby enriching the quality of learning in schools.